Homozygous hydroxymethylbilane synthase knock-in mice provide pathogenic insights into the severe neurological impairments present in human homozygous dominant acute intermittent porphyria. (7th January 2019) - Yasuda, Makiko; Gan, Lin; Chen, Brenden; Yu, Chunli; Zhang, Jinglan; Gama-Sosa, Miguel A; Pollak, Daniela D; Berger, Stefanie; Phillips, John D; Edelmann, Winfried; Desnick, Robert J
Abstract: Acute intermittent porphyria (AIP) is an inborn error of heme biosynthesis due to the deficiency of hydroxymethylbilane synthase (HMBS) activity. Human AIP heterozygotes have episodic acute neurovisceral attacks that typically start after puberty, whereas patients with homozygous dominant AIP (HD-AIP) have early-onset chronic neurological impairment, including ataxia and psychomotor retardation. To investigate the dramatically different manifestations, knock-in mice with human HD-AIP missense mutations c.500G>A (p.Arg167Glu) or c.518_519GC>AG (p.Arg173Glu), designated R167Q or R173Q mice, respectively, were generated and compared with the previously established T1/T2 mice with ~30% residual HMBS activity and the heterozygous AIP phenotype. Homozygous R173Q mice were embryonic lethal, while R167Q homozygous mice (R167Q +/+ ) had ~5% of normal HMBS activity, constitutively elevated plasma and urinary 5-aminolevulinic acid (ALA) and porphobilinogen (PBG), profound early-onset ataxia, delayed motor development and markedly impaired rotarod performance. Central nervous system (CNS) histology was grossly intact, but CNS myelination was delayed and overall myelin volume was decreased. Heme concentrations in liver and brain were similar to those of T1/T2 mice. Notably, ALA and PBG concentrations in the cerebral spinal fluid and CNS regions were markedly elevated in R167Q +/+ mice compared with T1/T2 mice. When the T1/T2 mice were administered phenobarbital, ALA and PBG markedly accumulated in their liver and plasma, but not in the CNS, indicating that ALA and PBG do not readily cross the blood–brain barrier. Taken together, these studies suggest that the severe HD-AIP neurological phenotype results from decreased myelination and the accumulation of locally produced neurotoxic porphyrin precursors within the CNS.